Patient's Perspective on Management of Chronic Pain Associated With Frequent Emergency Attendances and Psychiatric Diagnoses. (September 2019) - Leung, Kelvin; Arthur, Richard; Udo, Itoro
This case presents a patient's perspective of clinical care and management of chronic pain with a psychiatric component, the latter of which was not initially apparent to both patient and services. It aims to understand patient's experience of illness (part A), its effects on patient's family (part B), experience of care from liaison psychiatry (part C), service provision for persons with chronic pain and its often-neglected mental health aspect (part D), and patient's hopes for the future (part E). Early involvement of liaison psychiatry may target the interaction between physical and psychological factors and provide appropriate interventions across the health-care system.